Development of International Islamic University Malaysia-Micro Aerial Vehicle (IIUM-MAV) - Omar, Ashraf Ali; Cheong, Zi Jian (2009)
In this project the first IIUM-Micro Aerial Vehicle (IIUM-MAV) model was successfully designed, built and tested by team from the Department of Mechanical Engineering, IIUM. Problems related to stability, weight management, component selection, and thrust to weight ratio were faced during the early development of models, namely MAV1 to MAV5. Those problems were solved with the flying wing configuration incorporated into the latest models, i.e. MAV6 and MAV7. The span dimensions for the IIUM-MAV6 and -MAV7 were, 1 m and 0.5 m, respectively. The total weight of MAV6 is 197 grams, while MAV7 is 157 grams. The foam was the main material used to construct the IIUM-MAV. The electric micro R/C engine with maximum weight of 19 grams and maximum power output of 80 W was used. Both MAV6 and MAV7 were successfully tested and flew. The performance of MAV7 had been proven to be better than MAV6 in term of stability and maneuverability.